Signal change in BA17, 18 and 19: A comparative study of normal, glaucoma suspects and POAGpatients - Nurul Hanim, Nasaruddin; A N, Yusoff; Sharanjeet, Kaur (IOP Publishing, 2020)
Magnetic resonance signal change is expected to be different between normal, glaucoma suspect (GS) and Primary Open Angle Glaucoma (POAG) subjects. Functional magnetic resonance imaging (fMRI) technique was employed to investigate the differences. This multiple subject studies were carried out to characterize the percentage of signal change (PSC) in Brodmann Area (BA) 17, 18 and 19 of the visual cortex. The block designed fMRI was implemented. The subjects were requested to focus on the black and white checkerboard stimulus of the visual world (A, B and CD), visual field (EF) and visual area (G). The data were analysed using Statistical Parametric Mapping (SPM8) via Matlab platform. results showed that GS subjects have the highest PSC, followed by normal and POAG subjects. However, no significant difference was observed in PSC between BA17, 18 and 19 for normal, GS and POAG groups with p = 0.0869, p = 0.0688 and p = 0.2690, respectively. In conclusion, none of the BA can be suggested to be the most dominant area in responding to the visual stimuli used in this study.